Active Pla Packaging Films: Effect of Processing and the Addition of Natural Antimicrobials and Antioxidants on Physical Properties, Release Kinetics, and Compostability - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Lopez de Dicastillo-Bergamo, A; Patiño-Vidal, C; Velasquez, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The performance characteristics of polylactic acid (PLA) as an active food packaging film can be highly influenced by the incorporation of active agents (AAs) into PLA, and the type of processing technique. In this review, the effect of processing techniques and the addition of natural AAs on the properties related to PLA performance as a packaging material are summarized and described through a systematic analysis, giving new insights about the relation between processing techniques, types of AA, physical–mechanical properties, barriers, optical properties, compostability, controlled release, and functionalities in order to contribute to the progress made in designing antioxidant and antimicrobial PLA packaging films. The addition of AAs into PLA films affected their optical properties and influenced polymer chain reordering, modifying their thermal properties, functionality, and compostability in terms of the chemical nature of AAs. The mechanical and barrier performance of PLA was affected by the AA’s dispersion degree and crystallinity changes resulting from specific processing techniques. In addition, hydrophobicity and AA concentration also modified the barrier properties of PLA. The release kinetics of AAs from PLA were tuned, modifying diffusion coefficient of the AAs in terms of the different physical properties of the films that resulted from specific processing techniques. Several developments based on the incorporation of antimicrobial and antioxidant substances into PLA have displayed outstanding activities for food protection against microbial growth and oxidation. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.